2020
DOI: 10.1021/jacs.0c05286
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Gas Phase Organometallic Catalysis Supported Within Metal–Organic Framework Pores

Abstract: Metal–organic frameworks (MOFs) can act as a platform for the heterogenization of molecular catalysts, providing improved stability, allowing easy catalyst recovery and a route toward structural elucidation of the active catalyst. We have developed a MOF, 1, possessing vacant N,N-chelating sites which are accessible via the porous channels that penetrate the structure. In the present work, cationic rhodium­(I) norbornadiene (NBD) and bis­(ethylene) (ETH) complexes paired with both noncoordinating and coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 96 publications
1
45
0
Order By: Relevance
“…Diagnostic signals in the high‐field region of the 1 H NMR spectrum are attributed to agostic Rh⋅⋅⋅H−C interactions, and a Rh−H group [ δ =−29.04 ppm, J (RhH)=32 Hz] in the allyl hydride, 3 . Whereas similar butene complexes to 1 and 2 are formed from solid/gas reactions with Rh I σ‐alkane complexes having R 2 P(CH 2 ) 2 PR 2 ligands (R=Cy, [36] t Bu [20] ), tautomeric Rh III allyl hydrides that come from C−H oxidative cleavage have only been identified indirectly by mechanistic and DFT studies as higher‐energy intermediates in alkene double‐bond isomerization processes for these [36] and related MOF systems [37] . Here, we suggest the larger P−Rh−P ligand bite‐angle makes the Rh III oxidation state more accessible, [38] and this key intermediate can now be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnostic signals in the high‐field region of the 1 H NMR spectrum are attributed to agostic Rh⋅⋅⋅H−C interactions, and a Rh−H group [ δ =−29.04 ppm, J (RhH)=32 Hz] in the allyl hydride, 3 . Whereas similar butene complexes to 1 and 2 are formed from solid/gas reactions with Rh I σ‐alkane complexes having R 2 P(CH 2 ) 2 PR 2 ligands (R=Cy, [36] t Bu [20] ), tautomeric Rh III allyl hydrides that come from C−H oxidative cleavage have only been identified indirectly by mechanistic and DFT studies as higher‐energy intermediates in alkene double‐bond isomerization processes for these [36] and related MOF systems [37] . Here, we suggest the larger P−Rh−P ligand bite‐angle makes the Rh III oxidation state more accessible, [38] and this key intermediate can now be observed.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this issue, we employed anion metathesis of 1 ·[CuCl] with NaBr or NaI in dry methanol for 24 and 48 hours, respectively. 29,30 In both cases, EDX analysis of the crystals indicated that quantitative halide exchange had occurred (see Mn : Cu : X 3 : 1 : 1 ratios; X = Br, I; Table S3 and Fig. S20 † ).…”
Section: Resultsmentioning
confidence: 94%
“…33 SCXRD analysis revealed a linear AuCl complex coordinated to a single N-donor site in 1 (Figure 1, Figures S15, S16), and EDX analysis of the crystals (Table S2, Figure S17) confirmed the expected Mn:Au:Cl ratio of 3:1: with NaBr or NaI in dry methanol for 24 and 48 hours, respectively. 29,30 In both cases, EDX analysis of the crystals indicated that quantitative halide exchange had occurred (see Mn:Cu:X 3:1:1 ratios; X= Br, I; Table S3, Figure S20). Single crystal quality for the bromide and iodide exchanged MOFs was excellent, permitting their examination by SCXRD.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 95%
See 2 more Smart Citations